2009
DOI: 10.1021/es900760m
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interlayer Hydration in Lincomycin Sorption by Smectite Clays

Abstract: Lincomycin, an antibiotic widely administered as a veterinary medicine, is frequently detected in water. Little is known about the soil-water distribution of lincomycin despite the fact that this is a major determinant of its environmental fate and potential for exposure. Cation exchange was found to be the primary mechanism responsible for lincomycin sorption by soil clay minerals. This was evidenced by pH-dependent sorption, and competition with inorganic cations for sorptive sites. As solution pH increased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 38 publications
6
41
0
Order By: Relevance
“…K d (L/g) increased by 76% to 1.26 L/g from 0.30 L/g as the ionic strength decreased from 733 mM to 2.66 mM. An abundance of literature exists supporting the contention that ion exchange processes are strongly influenced by ionic strength (Sparks, 1995;Wang et al, 2009;Yang et al, 2009). Consequently, we conclude that denatonium sorbs to the smectite surfaces in a cation exchange process, where inorganic cations are replaced by denatonium ions.…”
Section: Effect Of Temperaturementioning
confidence: 67%
“…K d (L/g) increased by 76% to 1.26 L/g from 0.30 L/g as the ionic strength decreased from 733 mM to 2.66 mM. An abundance of literature exists supporting the contention that ion exchange processes are strongly influenced by ionic strength (Sparks, 1995;Wang et al, 2009;Yang et al, 2009). Consequently, we conclude that denatonium sorbs to the smectite surfaces in a cation exchange process, where inorganic cations are replaced by denatonium ions.…”
Section: Effect Of Temperaturementioning
confidence: 67%
“…Casey et al, 2004;Wang et al, 2009;Olshansky et al, 2011) Comparatively low partitioning coefficients (Kd) <2 have been reported for adsorption to aquifer sediments (Scheytt et al, 2005). These findings may have important implications for ionic EOC fate during changes in major ion chemistry (e.g.…”
Section: Surface Sorption and Eoc Molecular Propertiesmentioning
confidence: 99%
“…The amphiprotic character of silanol and aluminol groups in clays surfaces is responsible for a pH-dependent surface charge in clays (however, water molecules associated with exchangeable cations and clay surfaces may obscure these charged adsorption sites; such effect is dependent on the hydration strength of the exchangeable ions [170][171][172][173][174][175]). Electrostatic interactions with the surface and mechanisms such as cation exchange, cation bridging with the surface, surface complexation, and hydrogen bonding seem to be involved in the capture of ionic and polar species from aqueous media [121][122][123][124][125]176].…”
Section: Clay-based Materialsmentioning
confidence: 99%